(untitled) (Ukrainian Journal of Ophthalmology, 2025)
Purpose: To determine correlations between the grade of lens opacity and tear levels of total antioxidant activity (TAA) and lipid peroxidation (LPO) products in patients having both cataract and bacterial keratitis treated versus not treated with methyl-ethyl pyridinol hydrochloride (MH). Methods: Patients of the study group had both senile cataract and bacterial stromal keratitis; they received MH (nine four-week cycles of daily treatment with MH separated by four-week breaks) as an adjunct to the conventional antibacterial treatment. Patients that received the conventional antibacterial treatment only were used as controls. The development of senile cataract in patients with keratitis was followed up for 18 months. Severity of lens opacity was assessed by slit lamp biomicroscopy and scored on a scale of 0 to 5. Tear levels of TAA, malondialdehyde (MDA) and diene conjugate (DC) were determined in patients with keratitis only and those having both keratitis and cataract. Spearman’s rank correlation was used to determine associations between the grade of lens opacity and tear levels of metabolic characteristics. Results: Correlations between the grade of lens opacity and tear levels of TAA, MDA and DC were higher for patients having both cataract and keratitis and treated with MH than for patients with keratitis only. There were correlations of the grade of lens opacity with tear levels of TAA, MDA and DC (R=-0.85, R=0.80 and R=0.65, respectively) and of the tear level of TAA with tear levels of MDA and DC (R=-0.84 and R=-0.72, respectively) for patients having both cataract and bacterial keratitis and treated with MH. Conclusion: Our findings of apparent correlations of the grade of lens opacity with the parameters of the oxidative-antioxidatiove system in the tear fluid of patients indicate a pathogenetic role of bacterial keratitis in the development of cataract. MH has antioxidative properties and may be used for correcting metabolic abnormalities and preventing structural and functional changes in the lens in cataractogenesis with corneal inflammation.